The effect of the wandering exhibition strategy on divergent thinking among fourth-grade students in biology (Journal of the College of Basic Education, 2022)
The research aims to identify (the effect of the wandering exhibition strategy on divergent thinking among female students of the fourth scientific grade in biology) To verify this, the following null hypothesis was formulated: 1 - “There is no statistically significant difference at the (0.05) level between the average scores of the experimental group students who will study according to the roaming exhibition strategy and the average scores of the control group students who will study according to the usual method in the divergent thinking test.” Where the two researchers chose the middle school of the martyr Amna Al-Sadr affiliated with the General Directorate of Education in the province of Babil in an intentional way, and in the way of random assignment, Division (C) was chosen to represent the experimental group that will study biology according to the strategy of the roaming exhibition, and the number of its students is (30), while the division represented ( b) The control group that will study biology according to the usual method, and the number of its students (32) students. For the academic year ( 2021-2022 ) The two researchers determined the subject that will be studied during the period of application of the experiment, which is (6) chapters from the biology book for the fourth scientific class. After completing the experiment and application of the divergent thinking test and obtaining the results, the data were treated statistically using the t-test for two independent samples, and the following results were reached. The students of the experimental group who were taught according to the wandering exhibition strategy outperformed the students of the control group who were taught according to the usual method in the divergent thinking test. Therefore, the researcher recommends some recommendations and suggestions.